Penanaman Nilai Karakter Melalui Pendidikan Anak - Fauzan Fauzan (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Abstract: The value character is closely related to the growth process of a child. The stronger the character value habituation made through the process of education, will increasingly have a significant impact on growth and development. The value of character education is the responbility of all components involved in the educational process, the family (parents), society and environment, as well as the school become a critical success factor implantation on the character of a child. Keywords: children’s education, the value character.